Genome-scale Identification and Analysis of Genes Encoding Putative Light-harvesting Chlorophyll a/b binding Proteins in Potato (Solanum tuberosum L.) - Phi Bang Cao (Science Faculty of Chiang Mai University, 2019)
Light-harvesting complex proteins (LHCs) are essential photosynthetic pigment-binding components within the thylakoid membrane. These proteins are encoded by one of the most complex gene families in higher plants. They transfer light energy to photosynthetic reaction center and play a major role in photoprotection and abiotic stress tolerance in many plants. Here, we identified a total of 46 putative LHC encoding genes in potato (Solanum tuberosum) genome by using in silico approaches. Most of the LHC deduced proteins (38 out of 46) exhibit the Chloroa_b-bind (PF00504) conserved domain. The potato LHC genes were classified into groups based on the phylogeny analysis, including PSI (9 genes), PSII (26 genes), LHCrelated genes (5 genes), and light-inducible genes (6 genes). The PSI and PSI LHC genes were sorted into six subgroups and were designated as A1-A6 and B1-B6, respectively. Three PSI LHC subgroups contained two genes each, and three others are single-locus gene subgroups. Surprisingly, an expansion of B1 subgroup, resulting from recent gene duplication events, was observed in this crop genome. Generally, expression of most of the putative potato LHC genes was detected in leaves, except StLIL1. Moreover, the LHC genes were expressed more abundantly in aerial vegetative or reproductive tissues than underground tissues.